NURBS-Python: An open-source object-oriented NURBS modeling framework in Python - Bingol, Onur Rauf; Krishnamurthy, Adarsh (SoftwareX, 2019)
We introduce NURBS-Python, an object-oriented, open-source, Pure Python NURBS evaluation library with no external dependencies. The library is capable of evaluating single or multiple NURBS curves and surfaces, provides a customizable visualization interface, and enables importing and exporting data using popular CAD file formats. The library and the implemented algorithms are designed to be portable and extensible via their abstract base interfaces. The design principles used in NURBS-Python allows users to access, use, and extend the library without any tedious software compilation steps or licensing concerns.